A Systematic Investigation on Barriers and Critical Success Factors for Clinical Information Systems in Integrated Care Settings - Hoerbst, A.; Schweitzer, M. (Yearbook of Medical Informatics, 2015)
Objectives: Clinical Information Systems (CIS) have ever since the introduction of information technology in healthcare played an important role to support healthcare professionals and the process of treatment. With the rise of the concept of integrated care organizational borders, the sole focus on data aggregation or healthcare professionals as users disappear more and more. The manuscript discusses the concept of CISs and investigates critical success factors for CISs in the context of integrated care and in the course of time.Methods: In order to identify critical success factors and barriers for CISs a systematic literature review was conducted based on the results from PubMed and Cochrane, using MaxQDA. Search results were thereby limited to reviews or meta-analysis.Results: We have found 1919 references of which 40 met the inclusion criteria. The analysis of the manuscripts resulted in a comprehensive list of success factors and barriers related to CISs in integrated care settings. Most barriers were user-related whereas for the success factors an even distribution of organizational, technical and user-related factors was observed. The vast majority of publications was focused on healthcare professionals. Conclusion: It is important to incorporate experiences made/ collected over time, as the problems encountered seem to remain almost unvaried. In order to support further systematic investigations on the topic it is necessary to rethink existing concepts and definitions to realign them with the ideas of integrated care.
Keywords: Clinical information system; success factor; barrier; integrated care